Two Differently Regulated Nuclear Factor κ B Activation Pathways Triggered by the Cytoplasmic Tail of CD40 - Tsukamoto, Nobuo; Kobayashi, Norihiko; Azuma, Sakura; Yamamoto, Tadashi; Inoue, Jun-ichiro (Proceedings of the National Academy of Sciences - PNAS, 1999)
CD40 signaling modulates the immune response at least in part by activation of nuclear factor κ B (NFκ B). It has been shown that two distinct domains in the CD40 cytoplasmic tail (cyt), namely cyt-N and cyt-C, independently activate NFκ B. Although four members of the tumor necrosis factor receptor-associated factor (TRAF) family, including TRAF2, TRAF3, TRAF5, and TRAF6, bind to the CD40 cyt, how each TRAF protein contributes to the NFκ B activation by CD40 is not clear. Here we report that TRAF2, TRAF3, and TRAF5 bind cyt-C, whereas TRAF6 binds cyt-N. cyt-N is conserved poorly between human and mouse CD40, while cyt-C is highly conserved. However, single aa substitution of Glu-235 in cyt-N of human CD40 with Ala abolishes the binding of TRAF6 to cyt-N and NFκ B activation by cyt-N. Conservation of this Glu between mouse and human CD40 strongly suggests that TRAF6 could link cyt-N to signals essential for CD40-mediated immune response. Furthermore, NFκ B activation by cyt-C is inhibited by a kinase-negative form of NFκ B-inducing kinase more efficiently than that by cyt-N, consistent with the result that NFκ B activation by TRAF2 and TRAF5 is inhibited by a kinase-negative form of NFκ B-inducing kinase more efficiently than that by TRAF6. These results indicate that NFκ B activating signals emanating from cyt-N and cyt-C are mediated by the different members of the TRAF family and could be regulated in a distinct manner.